Pengaruh Ketimpangan Pendapatan, Tingkat Pendidikan dan Kemiskinan Terhadap Pertumbuhan Di Indonesia: The Influence of Income Inequality, Education Level and Poverty on Growth in Indonesia - Handayani, Nurvia; Hanifa, Nurul (Universitas Negeri Surabaya, 2024)
The background to the research is that the benefits of economic growth have not been felt evenly by the Indonesian population, income inequality is still a serious problem in Indonesia, the level of education in Indonesia is still relatively low compared to other countries and the poverty rate in Indonesia is still increasing. The aim of this research is to indicate the influence of income inequality, education level and poverty on economic growth in 34 provinces in Indonesia in 2020-2022. The research method used for analysis is panel data regression which is tested with the E-Views 12 analysis tool. Thus the result is that income inequality has a negative and significant influence on economic growth, whereas education level and poverty have a positive and significant influence on economic growth. Income Inequality, Education Level, Poverty, Economic Growth